Prevalence and risk factors of intestinal parasitic infections among pregnant women in Taiz Governorate, Yemen: A hospital-based study - Alharazi T. (Helminthologia, 2023)
Intestinal parasitic infections in pregnant women have been associated with severe adverse outcomes such as anemia, low birth weight, and mother and fetus morbidity and mortality. This study aimed to determine the prevalence of intestinal parasitic infection and its associated risk factors among pregnant women in Taiz, Yemen.